Concepciones iniciales sobre la asociación estadística - Estepa Castro, José Antonio; Batanero Bernabeu, Carmen (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1995)
In this paper we make a summary of psychological investigation about statistics association. The results of experimental study about previous conceptions are shown. This study has comprised the students' judgments of association. Using factorial analysis, we have identified five factors, which determine the structure of students' strategies. We also show a qualitative study about students' strategies in 2 x 2 and r x c contingency tables, scatterplots, and comparison of a numerical variable in different samples. Finally we describe four different misconceptions about statistical association and the conclusions of this paper.